AB1196 A REVIEW OF ELECTRONIC RHEUMATOLOGY REFERRALS AT THE QUEEN ELIZABETH UNIVERSITY HOSPITAL (GLASGOW, UK) AND HOW THIS HAS LED TO SERVICE IMPROVEMENTS. (June 2019) - Laws, Arrianne; Batool, Saira; Graham, Kay; Noor, Sajjad; Mitchell, James; Hannington, Laura; Ingram, Gareth; Bawa, Sandeep; Crosbie, David
Abstract : Background: Our department provides a service for inpatient Rheumatology reviews Monday to Friday, 9am to 4pm, with a guaranteed review timeframe of 48-72 hours. We work predominantly on the QEUH site, which comprises 1677 acute inpatient beds. We launched an electronic referral system for inpatient Rheumatology reviews in February 2018. Interspeciality referrals are an essential part of most inpatient stays. In a time of increasing service demand within the NHS it is important that we have an effective system to manage our time and resources 1, 2 . Electronic referrals allow us to audit our workload, our efficiency at reviewing patients and allow for accountability of both the referrer and reviewer, therefore improving patient safety 3 . Using a set proforma allows us to improve communication, the quality of the referral and triage effectively 4 . Objectives: We performed a baseline review of the new system. Methods: We reviewed all electronic referrals between 8.2.18 and 13.8.18. We collected data on demographics, timing, reasons for referral and outcomes. Results: There were 346 referrals (58.4% female, mean age 64 years). Most (78%) were made from medical wards; the mean number of referrals per month was 49.4. Referrals were most frequently made on Fridays (23%). Most were in-hours (81%). The most common reason for referral was: a request for review (212; 61.3%); phone advice (70; 20.2%); procedural requests (50; 14.5%). 207 referrals (59.8%) were made for new patients, 91 (26.3%) for patients known to Rheumatology prior to admission, and 48 (13.9%) for patients already seen during the current admission. 50% of procedures were performed on knees and 50% on other joints. 82% of patients were seen within 72 hours. Acute hot swollen joint was the commonest reason for referral of new patients (38%), followed by vasculitis (6%). Questions regarding pre-existing disease management (59%) or DMARD questions (24%) predominated amongst referrals for patients known to Rheumatology prior to this admission. Conclusion: The use of the electronic referrals system has made it simple to review the workload of our Rheumatology on-call service. We have used the data on 'reason for referral' to guide the topics for our educational meetings to improve patient management. We actively contribute to the procedural teaching on knee joint aspiration both in junior doctor's formal training sessions, and opportunistically on wards following referral. This is a core procedure required for training completion for medical trainees in the UK and should help reduce referrals and manage patients in a more time efficient and cost-effective manner. We have also improved documentation by recording the time, date and name of the reviewer in our electronic entry We intend to collect data in the same period this year, to assess changes in referral pattern in the 12 months since the system was initiated and the impact of our interventions. References: [1] Rheumatology in Scotland: The state of Play, BSR and SSR [2] Oliver O'Sullivan, James Bateman, Paresh Jobanputra; 172 Acute Rheumatology Referrals are Increasing: A Service Evaluation of more than 1000 Consecutive Acute Inpatient Referrals from a Tertiary Centre, Rheumatology, Volume 55, Issue suppl_1, 1 April 2016, Pages i131–i132 [3] Shephard E, Stockdale C, May F, et al. E-referrals: improving the routine interspecialty inpatient referral system.BMJ Open Quality 2018;7:e000249. doi:10.1136/bmjoq-2017-000249 [4] Scheibe eat al. Efficiency gains for Rheumatology Consultation using a novel electronic referral system in a safety-net health setting. Arthritis Care and Research 2015;Vol.67 pp.1158-1163 Disclosure of Interests: Arrianne Laws: None declared, Saira Batool: None declared, Kay Graham: None declared, Sajjad Noor: None declared, James Mitchell: None declared, Laura Hannington: None declared, Gareth Ingram: None declared, Sandeep Bawa Speakers bureau: Abbvie, Novartis, Lilly, UCB, David Crosbie Speakers bureau: AbbVie, Celgene, Lilly, Menarini, MSD, Novartis, Pfizer, UCB